Phenolic composition and biological activities of the in vitro cultured endangered Eryngium viviparum J. Gay - Ayuso, Manuel (2018)
Eryngium viviparum is an endangered species that requires management efforts based on complementary ex situ conservation strategies, such as in vitro culture. This study was carried out to evaluate the phenolic composition and the antioxidant, cytotoxic, and antimicrobial properties of E. viviparum aerial and root parts obtained by this micropropagation technique. The HPLC-DAD-ESI/MSn analysis showed that phenolic compounds were more abundant in the root (102 ± 4 mg g−1 extract) than in the aerial part (40.6 ± 0.8 mg g−1 extract) of the plant. The major compound was trans rosmarinic acid, followed by trans 3-O-caffeoylquinic acid. The root extract also showed higher antioxidant activity, with a result close to that of trolox in the thiobarbituric acid reactive substances (TBARS) formation inhibition assay, and a moderate toxicity to lung (NCI-H460), breast (MCF-7) and liver (HepG2) tumour cells. It was also more effective than ketoconazole against Penicillium ochrochloron. In turn, the aerial part extract inhibited Salmonella typhimurium more effectively than ampicillin. This study highlights E. viviparum as an unexplored source of bioactive compounds with potential application in the food, pharmaceutical, and other industrial sectors. Consequently, it promotes the interest of conserving this endangered species.